Pengaruh Religiusitas Terhadap Rasa Bersalah Pada Warga Binaan Di Lembaga Pemasyarakatan Perempuan Kelas IIA Martapura - Sapitri, Nurlita; Ariani, Lita; Handrianto, Ciptro (Jurnal Psikologi Terapan, 2023)
This study aims to examine the influence of religiosity on guilt feelings among female inmates in Class IIA Women's Penitentiary Martapura. The research involved 213 female inmates aged between 15 and 50 years old. The participants' guilt feelings were measured using a guilt feelings scale, while their religiosity was assessed using a religiosity scale. The collected data were analyzed using descriptive statistics and regression analysis. The findings indicated a significant positive correlation between religiosity and guilt feelings, suggesting that higher levels of religiosity were associated with increased guilt feelings. Regression analysis further confirmed the influence of religiosity on guilt feelings. The study also explored the influence of age, types of offenses, sentence duration, and length of incarceration on guilt feelings and religiosity. The results revealed variations in guilt feelings and religiosity based on these factors. These findings contribute to a better understanding of the relationship between religiosity and guilt feelings among female inmates, emphasizing the importance of religious factors in the correctional context.